Analisis Yuridis Hak Atas Tanah Akibat Perbuatan Melawan Hukum Penguasaan Tanah : Studi Kasus Putusan Nomor 267/Pdt.G/2020/PN Kpg - Florensia Calista Putri Tembu; Anak Agung Ayu Intan Puspadewi; I Gede Agus Kurniawan; I Gusti Ayu Eviani Yuliantari (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the increasing incidence of land disputes in Indonesia, particularly those arising from unlawful acts in the form of unauthorized land occupation, which generate legal uncertainty and result in both material and immaterial losses for rightful landowners. The growing number of such cases highlights the urgent need for fair and firm legal protection, especially when land occupation has occurred over a long period and complicates the recovery of ownership rights. This research specifically analyzes Decision Number 267/Pdt.G/2020/PN Kpg, a case involving the occupation of part of the plaintiff’s certified land by the defendant. The general objective of the study is to gain a comprehensive understanding of the legal mechanisms for restoring land rights affected by unlawful land occupation, while the specific objectives are to identify the form of the unlawful act committed and to analyze the legal process used to recover the disputed land rights. The research employs a normative legal method based on the analysis of secondary data, including legislation, legal doctrines, and court decisions. The approaches applied consist of statutory, conceptual, and case approaches, using juridical-descriptive analysis techniques. The findings are expected to identify unauthorized land occupation through boundary expansion as a form of unlawful act and to explain the recovery mechanism through civil litigation and the validation of land boundary re-measurement reports. This study is expected to contribute theoretically to agrarian and civil law development and practically to improving land dispute resolution procedures and public legal awareness.